The Effect of Storage Time and Temperature on Ascorbic Acid Content of Arumanis Mango Fruit (Mangifera indica) - Arguni, Medina Aminarti; Sandra, Yurika (Universitas Ibn Khaldun Bogor, 2025)
One of the most popular fruits in Indonesia is Arumanis mango, which has high levels of ascorbic acid. These levels can be influenced by storage time and temperature. The purpose of this study was to provide information about the effect of storage time and temperature on ascorbic acid levels of Arumanis mangoes. The research method used was laboratory experimental with a focus on arumanis mangoes exposed to different lengths of time (0, 2, 4, and 6 days) and temperatures (25°C and 5°C). The ascorbic acid content of the samples was then assessed using spectrophotometric methods. The collected data were analyzed using the two-way Anova test to detect the ascorbic acid content of arumanis mango fruit stored at various times and temperatures.The average ascorbic acid content of Arumanis mangoes stored at room temperature is 3.703%, while the average ascorbic acid content of Arumanis mangoes stored in the refrigerator is 5%. The ascorbic acid content decreased on days 2, 4, and 6 of storage in both temperature groups. The results of the two-way ANOVA test showed a p <0.05, indicating an interaction between storage duration and temperature in determining the ascorbic acid content of Arumanis mangoes. There is an interaction between storage duration and temperature in determining the ascorbic acid content of Arumanis mangoes. The longer the storage period, the lower the ascorbic acid content, while lower storage temperatures slow down the decrease in ascorbic acid content.